Heart Rate Variability during Nostril-Regulated Yoga Breathing: A Randomized Crossover Study - Shirley Telles; Alok Singh; Sachin Kumar Sharma; Acharya Balkrishna (International Journal of Yoga)
Background: Previous studies of nostril-regulated yoga breathing have focused on unilateral breathing with both inspiration and expiration through a specified nostril. However, traditionally described yoga breathing involves inspiration through one nostril and expiration through the other, called suryabhedan pranayama (SBP) (right nostril inspiration) and chandrabhedan pranayama (CBP) (left nostril inspiration). The effects of these practices were investigated here. Methods: Forty-seven healthy male participants (group mean age ± standard deviation [SD]; 26.34 ± 6.38 years) with prior experience of yoga breathing (group mean age ± SD; 43.64 ± 32.84 months) were randomly assigned to four sessions on separate days: (i) SBP, (ii) CBP, (iii) Breath awareness, and (iv) Quiet rest. The heart rate variability (HRV) and breath rate were recorded pre, during, and post each practice. Results: There was a significant increase in low frequency (LF) power and SD of NN intervals during SBP and CBP in comparison to the respective preceding (P < 0.05; repeated measures analyses of variance with Bonferroni adjusted post hoc analysis), while LF increased post-CBP alone. During both interventions, there were significant reductions in respiration rate. Conclusion: The changes in HRV suggest common rather than distinct changes in SBP and CBP suggestive of respiration-related increased cardiac parasympathetic activity. The involvement of both nostrils in SBP and CBP may have contributed to the comparable effects of the two practices.